Nanotechnology for Electronic Materials and Devices - Fiorenza, Patrick; Lo Nigro, Raffaella; Pécz, Béla; Eriksson, Jens (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Electronics nanotechnology represents a multidisciplinary field with a very broad range of applications used to address different challenges. This reprint, through eleven original research articles, aims to acknowledge recent developments related to the fabrication and applications of nanomaterials: synthesis, characterization, and device fabrication.